Prevention of the dystrophic phenotype in dystrophin/utrophin-deficient muscle following adenovirus-mediated transfer of a utrophin minigene. - Wakefield, P; Tinsley, J; Wood, M; Gilbert, R; Karpati, G; Davies, K (2000)
Duchenne muscular dystrophy (DMD) is a progressive muscle wasting disorder caused by the lack of a subsarcolemmal protein, dystrophin. We have previously shown that the dystrophin-related protein, utrophin is able to compensate for the lack of dystrophin in the mdx mouse, the mouse model for DMD. Here, we explore whether utrophin delivered to the limb muscle of dystrophin/utrophin-deficient double knockout (dko) neonatal mice can protect the muscle from subsequent dystrophic damage. Utrophin delivery may avoid the potential problems of an immune response associated with the delivery of dystrophin to a previously dystrophin-deficient host. Dko muscle (tibialis anterior) was injected with a first generation recombinant adenovirus containing a utrophin minigene. Up to 95% of the fibres continued expressing the minigene 30 days after injection. Expression of utrophin caused a marked reduction from 80% centrally nucleated fibres (CNFs) in the uninjected dko TA to 12% in the injected dko TA. Within the region of the TA expressing the utrophin minigene, a significant decrease in the prevelance of necrosis was noted. These results demonstrate that the utrophin minigene delivered using an adenoviral vector is able to afford protection to the dystrophin/utrophin-deficient muscle of the dko mouse. Gene Therapy (2000) 7, 201-204.